Occupational Stress and Family Functioning among Working Women of Sonitpur District, Assam - Munmi Neog; Nurnahar Ahmed; Sandeep Kollipara (Indian Journal of Psychiatric Nursing)
Background: Modern life is full of stress. Occupational stress is a type of psychological stress that affects not only employees' health and well-being but also the productivity of organizations. Working women are typically responsible for their homes while also meeting professional obligations. When a woman returns home under the stress and expectations of her career, she may encounter obstacles and difficulties in carrying out her domestic responsibilities. Aim: This study aimed to assess occupational stress and family functioning among working women, working in selected workplaces in Sonitpur district. Materials and Methods: A descriptive research design was adopted for the study. A total of seventy working women were selected through convenient sampling technique. Sociodemographic data were collected by administering a self-structured sociodemographic pro forma. Occupational stress and family functioning were assessed using standardized tools such as Occupational Stress Index and McMaster Family Assessment Device, respectively. Results: About 64.3% (f = 45) of the working women had a moderate level of occupational stress. Communication, roles, affective response, affective involvement, and behavior control domains of family functioning showed to be unhealthy. However, problem-solving and general functioning domains of family functioning were found to be healthy among working women. Conclusion: The study findings revealed that the majority of the working women have moderate level of occupational stress and unhealthy functioning in certain domains of family functioning.